Kinematics of Straight Right Punch in Boxing - Mahdi Cheraghi; Hamid Agha Alinejad; Ahmad Reza Arshi; Elham Shirzad (The Society of Aging and Physical Activity (SAPA), 2014)
The purpose of this study was to describe biomechanical parameters of head, upper and lower body extremities during a straight right punch throw related to performance and injury mechanism. Subjects were eight elite right-handed male (age 20.4 ± 2.1yrs; height 177.4 ± 8.5 cm; mass 70.4 ± 16.8 kg) amateur boxers. 3D motion analysis was used to assess the kinematics of the right side extremities and head. Ensemble averaging of time normalized kinematic parameters was used to have better visual inspection. Results showed a similar pattern between subjects with some considerable variation in some parameters that pointed out to individualized pattern in elite boxers. Investigation of lower body joints kinematics explained boxers throw punch using leg drive. Stretch-shortening cycle detected in the technique implies potential for performance enhancing using plyometrics. Head velocity measured in anterior-posterior and medial-lateral direction would intensify potential head injuries.